2020
DOI: 10.1007/s40145-020-0406-5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of MoSi2 on oxidation protective ability of TaB2-SiC coating in oxygen-containing environments within a broad temperature range

Abstract: TaB 2-SiC coating modified by different content of MoSi 2 was fabricated on graphite substrate with SiC inner coating by liquid phase sintering to elevate the anti-oxidation capability of the TaB 2-SiC coatings. As compared to the sample with the TaB 2-40wt%SiC coating, the coating sample modified with MoSi 2 exhibited a weight gain trend at lower temperatures, the fastest weight loss rate went down by 76%, and the relative oxygen permeability value reduced from about 1% to near 0. More importantly, the large … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(12 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…19,20 In our previous work, we have found that the MoSi 2 phase has a great influence on the enhancement of the oxidation inhibition ability of the generated compound glass layer. 21 Furthermore, we have prepared the HfB 2 -MoSi 2 -SiC coating by in situ synthesis method, which could protect the C/C composites from oxidation at 1773 K in air for 408 h, exhibiting good application potential. 22 Since the defects in the coating itself and the selfgenerated glass layer are the main oxygen diffusion channels, the dynamic stability of the coating to inhibit the generation of defeats greatly affects the oxygen blocking effect of the coatings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…19,20 In our previous work, we have found that the MoSi 2 phase has a great influence on the enhancement of the oxidation inhibition ability of the generated compound glass layer. 21 Furthermore, we have prepared the HfB 2 -MoSi 2 -SiC coating by in situ synthesis method, which could protect the C/C composites from oxidation at 1773 K in air for 408 h, exhibiting good application potential. 22 Since the defects in the coating itself and the selfgenerated glass layer are the main oxygen diffusion channels, the dynamic stability of the coating to inhibit the generation of defeats greatly affects the oxygen blocking effect of the coatings.…”
Section: Introductionmentioning
confidence: 99%
“…Among the silicides, MoSi 2 is not only an excellent glass‐forming substance, but also an outstanding sintering additive 19,20 . In our previous work, we have found that the MoSi 2 phase has a great influence on the enhancement of the oxidation inhibition ability of the generated compound glass layer 21 . Furthermore, we have prepared the HfB 2 ‐MoSi 2 ‐SiC coating by in situ synthesis method, which could protect the C/C composites from oxidation at 1773 K in air for 408 h, exhibiting good application potential 22 …”
Section: Introductionmentioning
confidence: 99%
“…Generally, C sf /UHTCs are prepared by ceramic processing, such as hot pressing [11][12][13], spark plasma sintering [14][15][16], pressureless sintering, and reactive melt infiltration (RMI). For the C sf /UHTCs composites fabricated by these conventional methods, there are two main bottlenecks.…”
Section: Introduction mentioning
confidence: 99%
“…However, ZrB 2 is challenging to achieve densification due to its strong covalent bond and low diffusion coefficient [11,12], which would also become porous during the oxidation process [13]. To suppress such defects, MoSi 2 , the most commonly used sintering additive, was generally used to increase the compactness of ZrB 2 [14,15]. Moreover, the excellent film-forming properties of MoSi 2 can effectively reduce the oxidation consumption of ZrB 2 , thus making the ZrB 2 -MoSi 2 coating present great potential [16][17][18].…”
Section: Introduction mentioning
confidence: 99%